SIMS: A QR Code-Enabled System for Locating, Monitoring, and Managing Office Supplies - Janny P Abu-abu; Leneisa Manua; Jayvee E. Maglasang; Renz Patrick Angelo R. Bison; Jelcy Omongos; Mark Rey Z. Embodo; Warnner Daminar Amin (MDP Student Conference, 2026)
: Inventory management in academic institutions frequently faces challenges including delays, inaccurate records, and a lack of transparency. To address these issues, this study developed SIMS: A QR Code–Enabled System for Locating, Monitoring, and Managing Office Supplies at USTP Panaon Campus. The system aims to improve supply monitoring, enhance visibility of custodianship, and provide a structured process for faculty requests. Using the Agile Software Development Life Cycle, the system was designed and evaluated through a mixed-method approach. Quantitative data were gathered using ISO/IEC 9126-based evaluation forms, while qualitative feedback was collected through interviews. Six respondents, including administrators and faculty, assessed the system’s functionality, usability, efficiency, maintainability, portability, security, and reliability. Results showed excellent ratings across all criteria, with weighted means of 5.0 for administrators and 4.90 for faculty, indicating strong performance in monitoring, usability, and security. These findings confirm that SIMS significantly improves operational efficiency, reduces human error, and promotes transparency in supply management. The study concludes that integrating QR code technology with web-based inventory systems provides a sustainable and scalable solution for institutional resource management. It is recommended to enhance the system with a mobile application for QR scanning during field operations and cloud-based backup for improved resilience.